PENERAPAN MODEL PROJECT BASED LEARNING (PJBL) TERHADAP MATERI DESAIN BUSANA PESTA FASE F DI SMK NEGERI 2 LAMONGAN - Latuconsina, Siti Amiya; Nashikhah, Ma’rifatun; Hidayati, Lutfiyah; Tri Rahayu, Imami Arum (Jurnal Socia Akademika, 2025)
Project Based Learning is a model where students take the lead in investigating and solving real-world problems, as well as developing and implementing their own ideas. This study aims to achieve two things including 1) description the implementation of Project Based Learning in the learning process, 2) description the level of creativity of phase F students after the implementation of Project Based Learning. This study uses a pre-experimental research type with a one-shoot case study design on 31 students of phase f of SMK Negeri 2 Lamongan. Observation and assessment are the methods used to collect data. LKPD sheets and implementation observation sheets are data collection techniques. Descriptive statistical tests, calculating the average score of PjBL implementation observations, and calculating the average creativity score are data analysis techniques. The results of the study showed that 1) the project-based learning approach produced a very good average of 89.43% in terms of teacher and student activity. 2) by using project-based learning, students were able to achieve a level of creativity of 89.51% in making party dresses, placing them in the very good category